Rice Bug (suggested common name) Leptocorisa acuta (Thunberg) (Insecta: Hemiptera: Alydidae) - Amelio Chi Serrano; Russell F. Mizell; Morgan A. Byron (EDIS)
Broad-headed bugs belong to a well-known but relatively small family of plant-feeding true bugs, usually seen feeding on the foliage and flowers of leguminous and graminaceous crops. Leptocorisa acuta (Thunberg) can be found on many crop plants in the family Poaceae (grasses), especially rice, and is a reported pest of economic significance in rice-producing countries like India, Australia, and China. This 3-page fact sheet was written by Amelio Chi Serrano, Russell F. Mizell, III, and Morgan A. Byron, and published by the UF Department of Entomology and Nematology, December 2014. (Photo: Lary E. Reeves, UF/IFAS)